The Liberty Journal. (Capelle a/d Ijssel : The Liberty Journal, 1993)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijksRedactie : PB 675, 2800 AR Gouda ; vanaf (1993) ? : PB 5169, 2900 ED Capelle a/d Ijssel
Nederlands
Periodiek